Analysis and Implementation of Unipolar PWM Strategies for Three Phase Cascade Multilevel Inverter Fed Induction Motor Drive - Ravikumar Bhukya; P. Satish kumar (Institute of Advanced Engineering and Science, 2018)
This paper presents unipolar pulse width modulation technique with sinusoidal sampling pulse width modulation are analyzed for three-phase five-level, seven-level, nine-level and eleven-level cascaded multi-level inverter. The unipolar PWM method offers a good opportunity for the realization of the Three-phase inverter control, it is better to use the unipolar PWM method with single carrier wave compared to two reference waves. In such case the motor harmonic losses will be considerably lower.The necessary calculations for generation of unipolar pulse width modulation strategies have presented in detail. The unipolar SPWM voltage switching scheme is selected in this paper because this method offers the advantages of effectively doubling the switching frequency of the inverter voltage. The cascaded multi level inverter fed induction motor is simulated and compared the total harmonic distroction for all level (five-level, seven-level, nine-level and elevel-level)of the inverter. Theoretical investigations were confirmed by the digital simulations using MATLAB/SIMULINK software.